Tropical Imaginings and Romantic Nostalgia: 75 Years of Giliw Ko and the Colonial Gaze - Amy Forbes (eTropic: electronic journal of studies in the tropics, 2016)
In 1998, Australia restored the 1939 film musical, Giliw Ko, the earliest extant film ever produced in the Philippines. Through its National Film and Sound Archive, Australia presented the film as a gift to the Filipino people to mark 100 years of independence. Celebrating its 75th year of production next year, the film as gift is ironical as it can be argued that the Philippines never gained independence, at least not from the strong colonizing effects of over 50 years of US rule. Giliw Ko tackles themes of a people’s infatuation and confusion over Hollywood images and what it means to be cultured and Westernized. In this essay, I explore American cinema’s historical and cultural constructs as a natural continuation of the colonialist project that is based on binary oppositions of West/East, civilized and uncivilized, conqueror and conquered. Utilising the film Giliw ko, I examine these constructs that are carried to the present day in Philippine cinema.